Integration of the Concept of Critical Awareness Paulo Freire in the Merdeka Curriculum: Efforts to Foster Critical Awareness of Students and Teachers - Durasa, Helfra; Suharta, I Gusti Putu; Lasmawan, I Wayan; Wijaksono, Cahyo Febri (National Dong Hwa University, 2024)
Implementing a Merdeka Curriculum in Indonesia has not been able to foster critical awareness among students and educators entirely. This research focuses on how integrating Paulo Freire's concept of conscientization in the Merdeka Curriculum can facilitate a more holistic and learner-centered approach to education. In this context, this study uses a literature review approach. The results showed that 1) The integration of critical awareness in the Merdeka Curriculum can be realized through problem-posing methods and dialogical methods emphasizing the importance of critical awareness and reflective action. 2) Applying this method can foster students' critical awareness in developing their knowledge more broadly, empowering students while respecting human values. 3) The involvement of all relevant parties in listening to and understanding the concerns of teachers and staff and active student involvement in the learning process can overcome teacher unpreparedness in implementing the Merdeka Curriculum. In addition, digital platforms and online learning resources can effectively provide education focusing on student empowerment and social awareness. Comprehensive training programs for educators are crucial to overcoming the diversity of teacher competencies.